2012
DOI: 10.1161/hypertensionaha.112.199026
|View full text |Cite|
|
Sign up to set email alerts
|

EP1 Disruption Attenuates End-Organ Damage in a Mouse Model of Hypertension

Abstract: PGE2 is a major prostanoid found in the kidney and vasculature contributing to the regulation of blood pressure. The PGE2 receptor EP1 has been shown to contribute to hypertension by mediating angiotensin II-dependent vasoconstriction, although its precise role is incompletely characterized. Disruption of the EP1 receptor in C57BL/6J mice reduced the incidence of mortality during severe hypertension induced by uninephrectomy, deoxycorticosterone acetate, and angiotensin II. Mortality was dependent on all compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…We and others have previously reported that the EP1 and EP3 receptors are vasoconstrictors, whereas the EP2 and EP4 receptors are vasodilators, indicating the PGE2/EPs system is essential for blood pressure regulation (3)(4)(5)(6). Increasing evidence also demonstrates that the PGE2/EPs system plays a critical role in vascular remodeling (7,8). EP4 appears to be important for both physiological and pathological vascular remodeling.…”
mentioning
confidence: 89%
“…We and others have previously reported that the EP1 and EP3 receptors are vasoconstrictors, whereas the EP2 and EP4 receptors are vasodilators, indicating the PGE2/EPs system is essential for blood pressure regulation (3)(4)(5)(6). Increasing evidence also demonstrates that the PGE2/EPs system plays a critical role in vascular remodeling (7,8). EP4 appears to be important for both physiological and pathological vascular remodeling.…”
mentioning
confidence: 89%
“…Ptger1 with its function of regulating blood pressure has also been associated with diabetes, preeclampsia, and premature birth; all three conditions can be associated with IUGR and have long-term fetal programming implications. Ptger1 is also known to mediate hypertension resulting in end organ damage (4).…”
Section: Differential Methylation Is Associated With Genes Related Tomentioning
confidence: 99%
“…EP1 receptor knockout mice display a reduced rise in mean arterial blood pressure in response to Ang II infusion and are protected against end-organ damage in hypertensive mouse models [20, 21]. Similarly, EP3 receptor knockout mice have a blunted blood pressure response to acute administration of Ang II [22].…”
Section: Introductionmentioning
confidence: 99%